Non-Cash Systems Improving Transparency in Village Financial Management: Sistem Non-Tunai Meningkatkan Transparansi Pengelolaan Keuangan Desa - Istanto, Hadi; Mursyidah, Lailul (Indonesian Journal of Law and Economics Review, 2024)
The specific background of this study revolves around the implementation of a non-cash transaction program in Randegan Village in collaboration with BPR Delta Artha to enhance financial management through SISKEUDES. A knowledge gap exists in understanding the effectiveness of non-cash systems in improving transparency and accountability in village financial management. This research aims to describe and analyze the implementation of the non-cash system within the SISKEUDES application in Randegan Village, Sidoarjo Regency. Utilizing a qualitative, descriptive approach, data collection involved interviews, observation, and documentation. The results indicate that vertical and horizontal communication is effective, facilities for operating SISKEUDES and non-cash applications are adequate, employee disposition toward policy implementation is positive, and bureaucratic cooperation is strong. The novelty of this study lies in its exploration of the interplay between communication, resource management, and bureaucratic structure in implementing a non-cash system for village financial management. The implications suggest that effective implementation of non-cash systems in village financial management can enhance transparency, accountability, and overall governance. Highlights: Effective Communication: Ensures smooth implementation of the non-cash system. Adequate Resources: Proper facilities and skilled staff support SISKEUDES' operation. Strong Bureaucratic Cooperation: Enhances the efficiency and transparency of financial management. Keywords: Non-Cash System, SISKEUDES, Village Finance, Management, Transparency